NURTURING DEAF CHILDREN THROUGH INCLUSIVE PARENTING PROGRAMS COMPREHENSIVE ANALYSIS FROM INTERNATIONAL DEAF AWARENESS WEEK AND THE INTERNATIONAL DAY OF SIGN LANGUAGE IN UGANDA- A CROSS-SECTIONAL STUDY. - Mulenzi, Tonny; Ikwara, Asher Emmanuel (Student's Journal of Health Research Africa, 2024)
Background Inclusive parenting for individuals with disabilities, particularly within deaf families, has garnered global attention. Understanding the unique challenges faced by these families is crucial for developing culturally sensitive interventions on a global scale. This qualitative research was conducted during Uganda's International Deaf Awareness Week 2023 to delve into the diverse context of the deaf population and highlight areas for targeted Parenting interventions. Methods The study employed in-depth interviews with 20 deaf parents and utilized NVIVO software for thematic content analysis. Rigorous ethical considerations were adhered to throughout the research process to ensure the integrity and reliability of the findings. The focus was on exploring the transformative potential of specialized parenting programs tailored to the needs of deaf families. Results The findings of the study underscored positive behavioral changes, improved education outcomes, increased awareness levels, and a sense of empowerment among the participants. Key success factors identified include peer support networks, cultural acceptance of deafness, recognition of technology's benefits, and a strong emphasis on sign language as a vital communication tool within deaf communities. Conclusion The study advocates for the implementation of tailored interventions that take into account the unique challenges faced by deaf families, particularly in African and Sub-Saharan contexts. The transformative impact of inclusive parenting programs, as highlighted during Uganda's International Deaf Awareness Week 2023, demonstrates the potential for positive changes in family dynamics and educational outcomes. Recommendations Recommendations include adopting a holistic approach that combines awareness campaigns, collaborative efforts between stakeholders, leveraging technology for accessibility, and promoting cultural sensitivity in educational and support programs. These strategies aim to empower deaf families globally and nurture deaf children through context-specific and inclusive strategies